The Effect of Training on the Quality of Patient Handoff from Emergency Medical Technicians to the Emergency Department of the Surgical Emergency Center: A Quasi-Experimental Study - Afsane Abdollahzade Sarvestani; Zahra Khademian; Zahra Molazem (مجله علوم پزشکی صدرا, 2024)
Introduction: Poor reporting during patient handoff from emergency medical technicians to the emergency department can threaten patients’ safety. This study aimed to determine the effect of training on the quality of patient handoff from emergency medical technicians to the emergency department of the surgical emergency center.Methods: This quasi-experimental study was conducted at Shahid Rajaee Surgical Emergency Center in Shiraz, Iran. The study sample included 80 emergency medical technicians with a mean age of 31.12±6.2 years, who were selected by simple random sampling and divided into two experimental and control groups by permuted block randomization. Data were collected by observing the handoff of three patients by each technician before and after the intervention with a rating scale developed by the researchers. The intervention consisted of a 4-hour training workshop about principles of patient reporting and handoff for emergency medical technicians. Data analysis was performed using descriptive statistics, chi-square, independent, and paired sample t-tests using SPSS version 20. The significance level was less than 0.05.Results: After the intervention, the mean score of patient handoff quality in the experimental group (29.94±2.73) compared to before the intervention (24.58±3.38, P<0.001) and compared to the control group (23.94±2.83, P<0.001) was significantly higher.Conclusion: The findings showed that reporting training to emergency medical technicians can help to improve the quality of their patients’ handoff to emergency departments.